Analisis Dampak Media Massa Terhadap Konflik Rohingya terhadap Respon Masyarakat Indonesia - Retno Wulandari; Edison Bonartua Hutapea (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the impact of mass media coverage on the Rohingya conflict and how media framing influences the response of Indonesian society. Using a qualitative approach through documentation studies, this research examines reports from various prominent online media such as Kompas.com, CNN.com, Liputan6.com, Detik.com, and BBC Indonesia. The analysis results show that mass media play a strategic role in shaping public perception through different framings, ranging from humanitarian framing, human rights violations, to security and rejection aspects. The dominant humanitarian framing successfully increases empathy and solidarity among Indonesians toward Rohingya refugees, while negative framing has the potential to cause tension and rejection. Furthermore, the media also influence public opinion regarding government policies related to conflict management. This study emphasizes the importance of mass media in constructing balanced and responsible narratives to encourage constructive social responses and support human rights protection.